A Study of Customer Advocacy and its Relationship with Trust on Facebook - Lu, Xiang (2014)
The traditional relationship marketing has evolved and expended to online social network (OSN), and a new and popular term named customer advocacy has emerged in this field naturally. As its name indicated, this term may combine with relevant marketing resources/ activities that drive to corporate effectiveness and efficiency (Lacey and Morgan, 2009), and behave in terms of information sharing, word-of-month online (eWOM), marketing research support, and purchase intention. Additionally, since trust is the antecedent of applying customer advocacy in relationship marketing, it appears that it has the possibility to influence these customer advocacy behaviours. Considering that Facebook is the most representative social network site (SNS) on OSN presently, this exploratory research aims to investigate current users’ customer advocacy on Facebook, and the influence of trust on advocacy behaviours described above on this website. First of all, this dissertation will introduce general information of research background. Second, it will provide a literature review containing a great and wide range of theoretical knowledge and practical research findings related to OSN, customer advocacy and its online behaviours, and trust. Third, it will principally focus on constructing a mix method by applying both interview and questionnaire to collect primary data, as well as the evaluation of sample design and primary data collection. Then, it will adopt reliability, mean and std. deviation, and correlation analysis of IBM SPSS statistic (version 20) to analyse data collected from the questionnaire, so statistical data has evidenced that there are positive and significant linear relationship between trust and advocacy behaviours in terms of eWOM, marketing research support, and purchase intention. Finally, it will provide some recommendations to firms to harness and promote customer advocacy behaviours accordingly.